Accounting Information Systems of Construction Company - Ika Ajiani; Baiq Dinda Puspita Ayu; Muhammad Haris Nasri (Universitas Islam Lamongan, 2023)
This study aims to design an accounting information system for construction companies in Indonesia. This research is a descriptive research that will describe problem analysis, needs analysis, and accounting information system design at one of the construction companies in Indonesia as a research sample. The results of the study have succeeded in contributing to the design of an accounting information system for construction companies and are expected to help and facilitate construction companies in Indonesia in handling every existing project and can provide the project information needed quickly and accurately.